1992
DOI: 10.1203/00006450-199206000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pancuronium Bromide on Cerebral Blood Flow Changes during Seizures in Newborn Pigs

Abstract: ABSTRACT. We investigated the effects of pancuronium bromide pretreatment on cerebral blood flow (CBF) during bicuculline-induced seizures in anesthetized piglets. Arterial blood pressure, gases, pH, cerebral electrocortical activity, and CBF (radioactive microsphere) were monitored at baseline, 10 min after administration of pancuronium (0.3 mg/kg i.v.; n = 9) or vehicle (normal saline; n = 8), and again at 5, 15, and 60 rnin after bicuculline (3 mg/ kg i.v.). No change in CBF from baseline was observed at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

1994
1994
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Increased CO production correlated with the increase in pial arteriolar diameter during the ictal episode (12). Inhibition of HO-2 activity in the brain by tin protoporphyrin (SnPP) or chromium mesoporphyrin greatly reduced the amplitude and the duration of the cerebral vasodilator response to seizures (12,34). Although SnPP also reduced neuronal activation during the ictal episode (31), the functional consequences of HO inhibition in cerebral microcirculation were of much greater potency compared with the neuronal effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Increased CO production correlated with the increase in pial arteriolar diameter during the ictal episode (12). Inhibition of HO-2 activity in the brain by tin protoporphyrin (SnPP) or chromium mesoporphyrin greatly reduced the amplitude and the duration of the cerebral vasodilator response to seizures (12,34). Although SnPP also reduced neuronal activation during the ictal episode (31), the functional consequences of HO inhibition in cerebral microcirculation were of much greater potency compared with the neuronal effects.…”
mentioning
confidence: 99%
“…Inadequate blood supply to the brain may contribute to seizure-induced neuronal damage and to the overall postictal state. During seizures, blood flow to the brain increases in patients (7, 9) and in animal models (11,34). In newborn piglets, neuronal activation at the onset of bicuculline-induced seizures is accompanied by the immediate increase in diameter of pial arterioles, major resistance vessels of the brain that determine the cerebral blood flow (30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial hypoxia and hypercapnia directly dilate the cerebral blood vessels, and arterial hypertension further increases the CBF due to the diminished pressure autoregulation. In contrast, anaesthesia, pancuronium paralyzation, and artificial ventilation largely alleviate the systemic effects of seizures [48] rather reflecting the state of electrographic seizures. The combination of anaesthesia, ventilation and muscle relaxation thus allows a more specific examination of seizure-induced cerebrovascular changes.…”
Section: Animal Models Of Neonatal Seizuresmentioning
confidence: 99%
“…The combination of anaesthesia, ventilation and muscle relaxation thus allows a more specific examination of seizure-induced cerebrovascular changes. Under these conditions, a number of studies have found that the CBF is significantly elevated during seizures [15,28,48,49] . These data suggest that altered blood gas levels and/or elevations in mean arterial blood pressure (MABP) are not essential for the development of ictal cerebral hyperaemia.…”
Section: Animal Models Of Neonatal Seizuresmentioning
confidence: 99%